Penerapan Nilai-Nilai Olahraga Dalam Menekan Kriminalitas Pada Pelajar - Wahyu Munandar; Aminuddin (Yayasan Habiburrahman Jamalu Bina Ummat, 2023)
Adolescence is known as the transition period from childhood to adulthood. At this time, mental and physical functions, especially the maturation of sexual functions, have undergone major and essential changes, so there is often turmoil in his mind, which is manifested in his behavior, such as sadness, depression, behind closed doors, and soon. very prominent at this time is a deep awareness of yourself. Socialization of activities, including providing material on the influence of sports in suppressing juvenile delinquency at SMA Negeri 14 Maros Moncongloe Bulu, Kec. Moncongloe, Kab. Maros Prov. South Sulawesi. on Monday, June 12, 2023, between 09:00 - 12:00 wita. A total of 38 participants participated in this activity, of which 25 participants Teenagers contain various impressions, some people say that teenagers are an ordinary group, no different from other human groups. While others think that teenagers are a group of people who often trouble the elderly. Others see adolescents as the human potential that needs to be utilized. The qualities and moral values that are considered to be contained in sports and physical activities are not internalized and projected into the daily lives of those who do or participate in these sports and physical activities, but the moral values that have been chosen. must be regulated, built, and changed The basic structure of reasoning for the individuals involved. Realized the importance of strengthening the character of moral values in children from an early age, then as a physical education teacher.